Turismo: Actividad Complementaria para la Educación - Galeano Terán, Alex; Lomas Tapia, Kennedy; Chamorro Gómez, Andrea (Tierra Infinita, 2019)
Currently, physical activities in educational institutions are carried out monotonously and with pre-established orders without complementing or seeking innovative activities for the academic development of students, limited tourism as an activity for the development of cognitive, physical, cultural skills and contact with nature, conditioning the development of the personality, despite these benefits do not apply complementary tourism activities in the current curriculum so they are the future spokespersons of sports tourism practice. This research aims to insert three tourism activities in the school curriculum. The objectives proposed in the proposal were: to evaluate if tourism is taken into account as a complete activity in the curriculum, and in turn to determine the affinity for complementary tourist activities in students to finally design a tourist instructional guide applicable to the educational reality. The methodology used was a quantitative investigation using a survey, taking as a sample the ten years of basic education of the Luis Ulpiano del Torre del Canton Otavalo institution. As results were obtained: that the tourist activities are not included in the educational curriculum, the affinity that the students have was favorable having more interest in the practice of boating, hiking, mountain biking to finally design an innovative proposal for basic education.